Repetitions in reserve: An emerging method for strength exercise prescription in special populations - Maroto-Izquierdo, S.; López-Ortiz, S.; Peñín-Grandes, S.; Santos-Lozano, A. (Strength and Conditioning Journal, 2025)
This review briefly outlines the benefits and limitations of traditional methods for prescribing resistance training (RT) exercise intensity (i.e., the percentage of 1 repetition maximum, velocity-based training, and rating of perceived exertion) for special populations based on mechanical and psychological indicators. Given these limitations, the repetition in reserve (RIR) method, which quantifies the discrepancy between potential and actual repetitions, has been proposed as a safer, more effective, and adaptable alternative to optimize RT in special populations. This study provides an overview of the main RIR scales used in scientific literature and synthesizes RIR validation studies. Although the validity and reliability of the RIR method have not been extensively tested across different special populations, and a scarcity of studies applying it in clinical contexts has been detected, this review proposes a practical application that integrates existing scales for prescribing RT in rehabilitation settings and for individuals with chronic health conditions. In conclusion, the RIR method shows promise for broader application in clinical settings, and further research is needed to validate its effectiveness in diverse population groups.